The association between serological and dietary vitamin D levels and hepatitis C‐related liver disease risk differs in African American and white males. Issue 1 (26th May 2013) - White, D. L.; Tavakoli‐Tabasi, S.; Kanwal, F.; Ramsey, D. J.; Hashmi, A.; Kuzniarek, J.; Patel, P.; Francis, J.; El‐Serag, H. B.
Summary Background Vitamin D may affect the severity of HCV‐related liver disease. Aim To examine the association between serum vitamin D levels and advanced liver disease in a multiethnic US cohort of HCV patients, and account for dietary and supplemental intake. Methods We measured serum 25‐hydroxyvitamin D levels and used FibroSURE‐ActiTest to assess hepatic pathology in a cohort of HCV‐infected male veterans. We estimated and adjusted for daily intake of vitamin D from diet using a Dietary History Questionnaire, and dispensed prescriptions prior to study enrolment. We used race‐stratified logistic regression analyses to evaluate the relationship between serum vitamin D levels and risk of advanced fibrosis (F3/F4–F4) and advanced inflammation (A2/A3–A3). Results A total of 163 African American (AA) and 126 White non‐Hispanics were studied. Overall, ~44% of AAs and 15% of Whites were vitamin D deficient (<12 ng/mL) or insufficient (12–19 ng/mL); 4% of AAs and 9% of White patients had an elevated level (>50 ng/mL). Among AAs, patients with elevated serum vitamin D levels had significantly higher odds of advanced fibrosis (OR = 12.91, P = 0.03) than those with normal levels. In contrast, AAs with insufficient or deficient levels had > two‐fold excess risk of advanced inflammation (P = 0.06). Among White males there was no association between vitamin D levels and advanced fibrosis (F3/F4–F4) or inflammation (A2/A3–A3) risk. Conclusions We observed potential differences in the association between vitamin D levels and degree of HCV‐related hepatic fibrosis between White and African American males. Additional research is necessary to confirm that high serum vitamin D levels may be associated with advanced fibrosis risk in African American males, and to evaluate whether racial differences exist in HCV‐infected females.